An Analysis of Cricket-Related Foot and Ankle Injuries (International Journal of Food and Nutritional Sciences, 2022)
Background: In India, cricket is without a doubt the most popular sport. It is a well-known international sport that is performed in more than 60 nations. Cricket injuries are extremely prevalent, despite the fact that it is a non-contact sport. Despite its widespread use, only five major cricket-playing nations—England, South Africa, Australia, New Zealand, and the West Indies—have gathered information on cricket-related injuries. Very little information is accessible from the subcontinent, which is now the center of all cricket-related activities.In the medical literature, there haven't been many articles about cricket injuries, and even fewer have concentrated on foot and ankle injuries. Before Orchard et al established standards for what would constitute a cricket injury, injury definitions were not clearly spelled out. This article reviews the research on cricket-related foot and ankle injuries.